Some theoretical and legal aspects of lawyers’ tax control in Republic of Poland - Borshchevskyy, Oleh (Actual problems of law (Aktual'ni problemi pravoznavstva), 2023)
Relevance of the study. The issue of tax control in the field of tax relations remains relevant both for the taxpayer and the state, and can be learned through the practice of neighboring countries that are part of the European Union. The purpose of the study is the analysis and theoretical-legal knowledge of certain aspects of the tax control of the lawyer in the Republic of Poland with the possibility of borrowing the experience of the European Union countries. Methodology. The research was carried out by the method of analysis of legal norms and scientific researches of Polish scientists. Results: The article analyzes individual requirements of Polish legislation in the field of tax control, presents the works of Polish scientists, discloses certain aspects and features of tax control of a lawyer, identifies problematic issues of a lawyer's tax audit related to the guarantees of legal practice, outlines the trends of the influence of control and the sphere professional activity.